Effects of Age, Gender, and Education on Income of Petty Traders in Dharan During COVID-19 Pandemic - Khatiwada, Sita Kumari (Journal of Management, 2023)
Petty trade refers to small-scale businesses operated by individual sellers on bicycles, carts, sheds, and small unorganized spaces. The epidemic of COVID-19 has had a great impact on the economy of Nepal like other countries. Therefore, the main objective of this study was to find out the effect of small businesses on household income due to COVID-19 in Dharan sub-metropolitan city. Data was collected through direct personal interviews with 48 people using a simple random sampling method. Collected data were analyzed through descriptive statistics using SPSS. The Pearson correlation test explains the relationship between different variables, the independent sample t-test-, and the ANOVA test for the hypothesis test. There is no significant relationship between household income and with age, gender, and education of petty traders. Similarly, this study concludes that the planners and policymakers of the Dharan sub-metropolitan city need to formulate appropriate policies and manage the business of the informal sector including small traders. The government should encourage programs that protect the economic rights of small traders and reduce various taxes imposed on them.